Left Field. - Leslie, Ian (New Statesman, 2019)
The author discusses Great Britain's political divide in 2019. Topics covered include how mistake theorists or Engineers attribute social problems such as homelessness and poverty to confusion and ignorance, the belief of conflict theorists or Warriors that problems are caused by oppression by a powerful group, and ways in which moral absolutism is the root of many evils. The Warrior mindset of British Labour Party leaders and their supporters is also mentioned.